Palliative Care Needs among Patients with End-Stage Kidney Disease: A Descriptive Observational Study - Fitriani Fitriani; Juwita Moreen Toar; Al Ihksan Agus; Rizka Wahyuni (PT.Mantaya Idea Batara, 2026)
Background: End-stage kidney disease (ESKD) represents an increasing health burden in Indonesia, with affected individuals experiencing complex needs that substantially diminish quality of life. Objective: aimed to identify palliative care needs among end-stage kidney disease patients undergoing hemodialysis. Methods: This cross-sectional study was conducted at a hemodialysis center in North Sulawesi in 2024. Respondents were selected using purposive sampling. The Sociodemographic Questionnaire and the Supportive and Palliative Care Indicators Tool (SPICT) were employed to collect sociodemographic data and identify potential palliative care needs. Univariate analysis was performed to examine palliative care needs among ESKD patients. Results: A total of 150 participants were included. Almost all respondents were identified as needing palliative care, with the majority presenting two general indicators and two clinical indicators. Conclusion: Nearly all patients with end-stage kidney disease undergoing haemodialysis are identified as having palliative care needs. This finding suggests the need to integrate routine palliative care assessment and services into patients with end- stage kidney disease, especially those in haemodialysis care to ensure comprehensive and patient-centered management of physical, psychosocial, and spiritual needs.